Black women's experiences of gendered racial sexual objectification, body image, and depressive symptoms. (June 2022) - Stanton, Alexis G.; Avery, Lanice R.; Matsuzaka, Sara; Espinel, Sarah
Abstract: Black women navigate unique sexual objectification experiences and concerns about their bodies as a consequence of the race- and gender-based marginalization that they face. However, less is known about the influence of gendered racial sexual objectification experiences on Black women's mental health (i.e., depressive symptoms) or the contributions of key body image indicators (i.e., body surveillance and current-ideal body image discrepancy) that reflect Black women's engagement in monitoring and managing their bodies. We surveyed 1595 Black women to test our hypotheses that experiences of gendered racial sexual objectification (i.e., frequency and stress appraisal) would be positively associated with depressive symptoms and that body surveillance and current-ideal body image discrepancy would moderate this association. Analyses showed that more frequent experiences of gendered racial sexual objectification and higher stress appraisal of these experiences were significantly associated with more depressive symptoms. Furthermore, body surveillance and current-ideal body image discrepancy moderated the relation between gendered racial sexual objectification and depressive symptoms. Findings highlight how Black women's objectification and increased engagement in body monitoring and management practices are associated with their experiences of depressive symptoms, and thus, may negatively influence their mental health. Highlights: Black women have distinct, racialized and gendered sexual objectification experiences and body image concerns. Body surveillance and current-ideal body image discrepancy are key predictors of Black women's mental health. Collectively, Black women's sexual objectification and body monitoring are associated with depressive symptoms.